Guidance relative to job satisfaction of home economics teachers - Dutcher, Mary Ault, author; Comstock, George A., advisor; Heilig, Herb, committee member; Novak, Benjamin J., committee member; Guard, Harris T., committee member; Williamson, Maude, committee member (Colorado State University. Libraries, 1948)
To view the abstract, please see the full text of the document.
Keywords: Teachers; Home economics -- Study and teaching